Pemberian Kredit Modal dan Investasi Untuk Pengembangan Usaha yang Berkelanjutan pada Dian’s Songket - Putu Ayu Sriasih Wesna; I Wayan Kartika Jaya Utama; Indah Permatasari; I Nyoman Putu Budiartha; I Made Suwitra; Johannes Ibrahim Kosasih; I Wayan Wesna Astara; Ni Luh Made Mahendrawati; I Nyoman Sujana; I Nyoman Sukandia; Anak Agung Istri Agung; I Made Pria Dharsana; I Nyoman Alit Puspadma; Ryskiaden Markus; Tjokorda Gede Agung Sayogaditya Widya Pramana Putra; Miel S. Bongon; Marcelo Roland C. Villafuerte; Demosthenes B. Vibandor; Leovigildo C. Sentelices; Carlos M. Raymundo (Postgraduated Community Service Journal, 2025)
Dian's Songket which started its business in 1995 which is engaged in the weaving industry of songket and endek woven fabrics. Dian's Songket in running its business faces various challenges in an effort to develop its business. One of the main problems faced is the limitation of capital. The purpose of the Community Partnership Program activity is to provide socialization of the importance of providing capital credit so that the sustainability of the business can grow rapidly. And it can provide benefits, namely that Partners can better understand the importance of providing capital credit so that the sustainability of their business can grow rapidly. The implementation of service activities at Dian's Songket begins with direct observation and then an analysis of legal needs, socialization and legal education for business owners and managers, preparation of conflict or dispute resolution procedures as well as evaluation and documentation of service activities. This socialization took place comprehensively from sharing knowledge owned by the PKM team or several questions from Dian's Songket itself. So that in the implementation of this PKM can help Dian's Songket to better understand several elements that must be held in the form of a sense of trust, agreement between the parties, the period given, risks that will occur and remuneration that must be carried out so that from these elements the Bank as a creditor can later help to provide capital credit back for Dian's Songket to develop its sustainable business.